Socio-Technical Imaginaries of Cultural Transformation Toward Sustainable Development - Dziubaniuk, Olga; Ivanova-Gongne, Maria; Narayan, Rumy (Springer, 2023)
It is becoming evident that an important aspect of internationalization of business is conducting activities that address issues related to the Sustainable Development Goals in developing markets. When conducting such activities international businesses often partner with local stakeholders for developing solutions and managing such multi-stakeholders for achieving sustainability goals. Effective partnering and management of multi-stakeholder networks call for a collective visioning process that captures the communities’ expectations and imaginaries for a shared understanding of technological and related social changes accompanying the implementation of development projects. The objective of this research is to shed light on how multi-stakeholder networks with diverse cultural moorings could be mobilized through socio-technical imaginaries for orchestrating activities required for implementing developmental projects. This study uses an empirical setting to showcase specifics of culture shaping socio-technical imaginaries of technologies for sustainability and their role in influencing cultural practices of local communities. The contribution of this research highlights the agential role of infrastructure in transforming culture through associated imaginaries. The imaginaries in this case are materialized through the design, construction, and operation of the water supply infrastructure which embodies certain morals, values, and norms. In revealing certain cultural practices that hinder ideas of well-being, the infrastructure triggers their transformation.
Keywords: Multi-stakeholder network; Sustainable Development Goals; Socio-technical imaginaries; Cultural schemas; Nepal; sustainable development; developing countries; fi=Strateginen johtaminen|en=Strategic Management|